2012
DOI: 10.4172/scientificreports.121
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices (KAP) Related to Pre-Conception & Pre-Natal Diagnostic Techniques (PC & PNDT) Act Among the Antenatal Women in Bikaner

Abstract: It was a population based cross sectional study done with the objective of Knowledge, Attitude and Practices (KAP) Related to Pre-Conception & Pre-Natal Diagnostic Techniques (PC & PNDT) act among the Antenatal Women in Bikaner district. A population of antenatal women 1000 preference of male child an indicator of gender discrimination was seen, it correlated with female age, literacy, their socioeconomic status, parity. After a detailed the present study showed a clear picture of factors affecting the knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
3
6
1
Order By: Relevance
“…Majority were happy with both the sex of the child whether boy or girl don't bother. This was similar to the study done by Sonal R Deshpande et al where no association was found between literacy status and socioeconomic class of the study subjects and preference to male child as opposed to the study by Srivastav et al (9) and Khatri M et al (10) where unawareness regarding PCPNDT Act and preference for male child was significantly associated with the literacy status of females.…”
Section: Jmscr Vol||06||issue||05||page 904-909||maysupporting
confidence: 89%
“…Majority were happy with both the sex of the child whether boy or girl don't bother. This was similar to the study done by Sonal R Deshpande et al where no association was found between literacy status and socioeconomic class of the study subjects and preference to male child as opposed to the study by Srivastav et al (9) and Khatri M et al (10) where unawareness regarding PCPNDT Act and preference for male child was significantly associated with the literacy status of females.…”
Section: Jmscr Vol||06||issue||05||page 904-909||maysupporting
confidence: 89%
“…Similar to study in Bikaner where 52.4% of the antenatal women were aware of PNDT act. 11 The awareness regarding the act was higher in our study compared to Srivastav et al in UP where only 32% were aware of PNDT act. 10 The reason for higher awareness in our study may be that the Srivastava study was done one decade earlier in 2001 and at that time the literacy status was comparatively much lesser and also in the last decade (2001-2010) mass media has played a significant role for increasing awareness.…”
Section: Discussioncontrasting
confidence: 51%
“…Analyzing education and attitude S. Ghose et al 9 and Khatri M, et al 11 in their study showed that up to graduation level, increase in education is accompanied with an improvement in the attitude in these ante-natal women. In our study we observed that there is increasing trends of right attitude about PC & PNDT Act is seen with increasing Literacy status.…”
mentioning
confidence: 99%
“…4 A study from Rajasthan showed that the overall knowledge about PNDT act was present among 52.4% of their participants. 3 Doubts' regarding safety of ultrasound is persisting in all societies. Studies have shown that patients considered that too many ultrasound may be harmful to the baby and also had belief that ultrasound could cause cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of media coverage, the knowledge regarding PNDT act among antenatal women in studies from Rajasthan and Mumbai were found to be only 52.4% and 34.3% of their study population. 3,4 Being a technology that is widely available, doubts' regarding its safety and usefulness is still persistent in antenatal mothers. The purpose of this study is to evaluate the knowledge of antenatal mothers regarding the uses of ultrasound during pregnancy and also to assess their attitude towards ultrasound.…”
Section: Introductionmentioning
confidence: 99%